Vector Resolved Energy Fluxes and Collisional Energy Losses in Magnetic Nozzle Radiofrequency Plasma Thrusters - Emoto, Kazuma; Takahashi, Kazunori; Takao, Yoshinori (Frontiers in Physics, 2021)
Energy losses in a magnetic nozzle radiofrequency plasma thruster are investigated to improve the thruster efficiency, which are calculated from particle energy losses in fully kinetic simulations. The simulations calculate particle energy fluxes with a vector resolution including the plasma energy lost to the dielectric wall, the plasma beam energy, and the divergent plasma energy in addition to collisional energy losses. As a result, distributions of energy losses in the thruster and the ratios of the energy losses to the input power are obtained. The simulation results show that the plasma energy lost to the dielectric is dramatically suppressed by increasing the magnetic field strength and the ion beam energy increases instead. In addition, the divergent ion energy and collisional energy losses account for approximately 4–12% and 30–40%, respectively, regardless of the magnetic field strength.